Asistensi “Green Education From” Pesantren - Adi Gunawan; Ach. Rifai; Suhaimi Suhaimi; Gatot Subroto; Febrina Heryanti; Sapto Wahyono (ALKHIDMAH: Jurnal Pengabdian dan Kemitraan Masyarakat, 2024)
The negative impact of environmental degradation is increasingly clear to us, hot air, groundwater deficit, long drought and other forms of natural disasters as a result of the decline in environmental quality. We must overcome the environmental damage in various ways that are relevant for the survival of future life. One way that is very potential, effective and efficient is to instill love and culture of environmental conservation in the pesantren environment. One of the pesantren Sumenep Madura that actively implements the green education program from pesantren, by implementing green education, cultivating greening and recycling waste, by maximizing the potential of around four thousand students from various regions and educational and social circles. By involving parties outside the pesantren with planned cooperation, the program is very helpful in educating students with an environmental perspective. By focusing the method on practical activities, students can more easily understand and implement these programs.